So help me golf : why we love the game - Reilly, Rick (Hachette Books, 2022)
"Beloved bestselling author and golf aficionado Rick Reilly channels his insatiable curiosity, trademark sense of humor, and vast knowledge of the game in a treasure trove of original pieces about what the game has meant to him and to others"--